ADRENAL GLAND TLR EXPRESSION IN ApoE DEFICIENT HOMOZYGOUS (ApoE KO-/-) MICE WITH IMPAIRED THYROID FUNCTION - Tripunoski, Toni; Panov, Sasho; Shumkovska, Jasmina Dimitrova; Josifovska, Slavica; Petrova, Irena Kostadinova; Ugrinska, Ana; Stojanoski, Sinisa; Manevska, Nevena; Stanojevic, Verdi; Rizova, Bojana Stoilovska; Popgjorceva, Daniela (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
The main aim of our study was to investigate the expression of TLR receptors in the adrenal gland of ApoE knockout mice in context of ApoE deficiency as well as impaired thyroid function (hypo- and hyperthyroidism). The study was conducted on two following experimental animal groups: hypothyroid homozygous mice ( ApoE KO -/- ) treated with PTU; hyperthyroid homozygous mice ( ApoE KO -/- ) treated with L-thyroxine (T 4 ) and two control groups: euthyroid homozygous mice ( ApoE KO -/- ) and euthyroid wild-type C57BL/6 mice (Bb). Determination of TLR gene expression in the adrenal gland was performed by RT-PCR reaction with semi-quantitative detection of populations of mRNA molecules transcribed from the TLR2, TLR4 and TLR9 genes in the adrenal gland in the treated experimental groups and the two untreated control groups. The results of our study are in support of the hypothesis that both conditions of impaired thyroid function produce TLR agonists that increase the expression of TLR in the adrenal gland (p<0,05). Also, in the untreated/control group of mice ( ApoE KO -/- ), an increased expression of TLR was found compared to the wild strain C57BL/6 mice (Bb) as a control group (p<0.001). Keywords: TLR receptors, adrenal gland, ApoE deficiency, Hypothyroid, Hyperthyroid.